2023
DOI: 10.1002/tox.23868
|View full text |Cite
|
Sign up to set email alerts
|

Female‐to‐male differential transcription patterns of miRNA‐mRNA networks in the livers of dioxin‐exposed mice

Abstract: Non‐coding microRNAs (miRNAs) have important roles in regulating the expression of liver mRNAs in response to xenobiotic‐exposure, but their roles concerning dioxins such as TCDD (2,3,7,8‐Tetrachlorodibenzo‐p‐dioxin) are less clear. This report concerns the potential implication of liver (class I) and circulating (class II) miRNAs in hepatotoxicity of female and male mice after acute exposure to TCDD. The data show that, of a total of 38 types of miRNAs, the expression of eight miRNAs were upregulated in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…As a prototype of halogenated aromatic compounds, TCDD is frequently employed to illustrate the toxicological effects of dioxins on organisms. Numerous studies have reported that TCDD induces a range of toxicological effects, encompassing reproductive, developmental, and carcinogenic impacts in both exposed individuals and a diverse array of experimental animal models ( White and Birnbaum, 2009 ; Faiad et al, 2022 ; Aldeli et al, 2023 ; Faiad et al, 2023 ; Hammoudeh et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a prototype of halogenated aromatic compounds, TCDD is frequently employed to illustrate the toxicological effects of dioxins on organisms. Numerous studies have reported that TCDD induces a range of toxicological effects, encompassing reproductive, developmental, and carcinogenic impacts in both exposed individuals and a diverse array of experimental animal models ( White and Birnbaum, 2009 ; Faiad et al, 2022 ; Aldeli et al, 2023 ; Faiad et al, 2023 ; Hammoudeh et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%